2015
DOI: 10.1111/jam.12973
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of using experimental infectivity data in risk assessment for Ebola virus: why ecology may be important

Abstract: SummaryAnalysis of published data shows that experimental passaging of Zaire ebolavirus (EBOV) in guinea pigs changes the risk of infection per plaqueforming unit (PFU), increasing infectivity to some species while decreasing infectivity to others. Thus, a PFU of monkey-adapted EBOV is 10 7 -fold more lethal to mice than a PFU adapted to guinea pigs. The first conclusion is that the infectivity of EBOV to humans may depend on the identity of the donor species itself and, on the basis of limited epidemiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…It is proposed here that these failures to demonstrate experimental infection in arthropods with low challenge doses in small numbers of arthropods do not provide definitive proof that arthropods are refractory to filovirus infection or that filoviruses do not originate from an arthropod source. Indeed, by analogy to trends in the numbers of LD 50 /pfu with passaging of EBOV in mammals (Gale et al., ), it is suggested that much higher doses of virus than the 300–1200 pfu per individual arthropod used by Swanepoel et al. () and Turell et al.…”
Section: Challenging the Current View That Filoviruses Cannot Infect mentioning
confidence: 98%
See 2 more Smart Citations
“…It is proposed here that these failures to demonstrate experimental infection in arthropods with low challenge doses in small numbers of arthropods do not provide definitive proof that arthropods are refractory to filovirus infection or that filoviruses do not originate from an arthropod source. Indeed, by analogy to trends in the numbers of LD 50 /pfu with passaging of EBOV in mammals (Gale et al., ), it is suggested that much higher doses of virus than the 300–1200 pfu per individual arthropod used by Swanepoel et al. () and Turell et al.…”
Section: Challenging the Current View That Filoviruses Cannot Infect mentioning
confidence: 98%
“…via an insectivorous bat) from an insect reservoir. Indeed, it is well known that the lethal dose 50% (LD 50 )/pfu ratio for EBOV varies hugely with passaging in mammalian species (guinea pigs) (see Gale et al., ). For example, analysing data from Ryabchikova et al.…”
Section: Challenging the Current View That Filoviruses Cannot Infect mentioning
confidence: 99%
See 1 more Smart Citation
“…An additional complication is that the pathogen may adapt to the new host, such that its infectivity increases. This is well established for filoviruses in laboratory animals where the infectivity per plaque-forming unit (pfu) may change by several orders of magnitude with passaging (Gale et al, 2016), and has recently been demonstrated for EBOV Makona adapting to humans through an amino acid substitution in its glycoprotein during the recent catastrophic outbreak in West Africa (Diehl et al, 2016;Urbanowicz et al, 2016). That outbreak also raised many questions regarding the unknown potential for companion animals (cats and dogs) to serve either as a reservoir or vector for the virus and so be involved in transmission of EBOV to humans and other animals.…”
mentioning
confidence: 99%
“…Indeed, it has been proposed that the infectivity to humans of an EBOV pfu may differ not only from bushmeat samples from different wildlife species (e.g. fruits bats and nonhuman primates) but also from different individuals of the same species depending on the degree of host adaptation (Gale et al, 2016). In effect no two pieces of bushmeat from EBOVinfected wildlife may be the same in terms of infectivity to humans, although this remains to be proved.…”
mentioning
confidence: 99%